Biosynthesis of the leucine derived α‐, β‐ and γ‐hydroxynitrile glucosides in barley (Hordeum vulgare L.). (31st August 2016) - Knoch, Eva; Motawie, Mohammed Saddik; Olsen, Carl Erik; Møller, Birger Lindberg; Lyngkjær, Michael Foged
Summary: Barley ( Hordeum vulgare L.) produces five leucine‐derived hydroxynitrile glucosides (HNGs), of which only epiheterodendrin is a cyanogenic glucoside. The four non‐cyanogenic HNGs are the β‐HNG epidermin and the γ‐HNGs osmaronin, dihydroosmaronin and sutherlandin. By analyzing 247 spring barley lines including landraces and old and modern cultivars, we demonstrated that the HNG level varies notably between lines whereas the overall ratio between the compounds is constant. Based on sequence similarity to the sorghum ( Sorghum bicolor ) genes involved in dhurrin biosynthesis, we identified a gene cluster on barley chromosome 1 putatively harboring genes that encode enzymes in HNG biosynthesis. Candidate genes were functionally characterized by transient expression in Nicotiana benthamiana . Five multifunctional P450s, including two CYP79 family enzymes and three CYP71 family enzymes, and a single UDP‐glucosyltransferase were found to catalyze the reactions required for biosynthesis of all five barley HNGs. Two of the CYP71 enzymes needed to be co‐expressed for the last hydroxylation step in sutherlandin synthesis to proceed. This observation, together with the constant ratio between the different HNGs, suggested that HNG synthesis in barley is organized within a single multi‐enzyme complex. Significance Statement: Leucine‐derived hydroxynitrile glucosides (HNGs) act as potential defense compounds. Here we identified a gene cluster encoding the enzymes needed for HNG biosynthesis, namely cytochrome P450s and UDP‐glucosyltransferases, thus supporting the idea that HNG biosynthesis in barley is organized within a single multi‐enzyme complex.